Detection of Ectoparasites in Farmed Striped Catfish (Pangasius hypophthalmus) in Karangpilang, Surabaya, Indonesia - Nadilla Chrisantya Yusuf Putri; Tri Suwanti, Lucia; Hadi Warsito, Sunaryo; Retno Lastuti, Nunuk Dyah; Rahardjo, Dadik; Aryaloka, Suhita (Veterinary Biomedical and Clinical Journal, 2023)
This research aimed to identify ectoparasites infecting farmed striped catfish in Karangpilang Surabaya, Indonesia. Individual catfishes with visible lesions on the body surface and abnormal behaviors were included in the study. Mucilage samples of 90 fishes were examined under a microscope for the presence of ectoparasite on the body surface of the fish, in the area of gills, skins, fins, and tails. Gills were cut with scissors and combed with a tweezer. Skin and fin were also scrapped with a sterile scalpel. The mucus obtained was put on an object glass and was observed under the microscope. The fish pond water was analysed for Oxygen Demand (DO), pH and temperature three times two weeks apart, starting from the day of fish sampling. Results showed that 42.2% (n=90) of samples were infected by ectoparasites. The ectoparasites identified were Gyrodactylus sp., Dactylogyrus sp., Trichodina sp. and Chilodonella sp. Fish pond water in the study site was of suitable quality for the growth of catfish. This study suggested that pathogens other than ectoparasites play roles in the development of pathologic conditions of stripped catfishes in the study area.